Triply-bonded indiumphosphorus molecules: theoretical designs and characterization. Issue 33 (10th April 2017) - Lu, Jia-Syun; Yang, Ming-Chung; Su, Ming-Der
Abstract : The theoretical results indicate the connected substituents (R) play a decisive role in determining both the kinetic and the thermodynamic stability of triple-bonded RInPR molecules. Abstract : The effect of substitution on the potential energy surfaces of triple-bonded RInPR (R = F, OH, H, CH3, SiH3, NHC, SiMe(Si t Bu3 )2 and SiiPrDis2 ) species was investigated, using the density functional theory ( i.e., M06-2X/Def2-TZVP, B3PW91/Def2-TZVP and B97-D3/LANL2DZ+dp). The theoretical results suggest all of the triple-bonded RInPR molecules prefer to adopt a bent form with an angle (∠In–P–R) of about 90°. Present theoretical evidence suggests only the bulkier substituents, in particular for the strong donating groups (such as the NHC group), can greatly stabilize the InP triple bond. In addition, bonding analyses demonstrate the bonding character of such triple-bonded RInPR compounds should be represented as . That is to say, the InP triple bond contains one traditional σ bond, one traditional π bond, and one donor–acceptor π bond. As a consequence, the theoretical findings strongly suggest the InP triple bond in acetylene analogues (RInPR) should be very weak.